Poetry and Secrecy. Issue 1 (3rd August 2018) - Walton, Jo; Luker, Ed
Abstract : In this editorial essay for a special issue of The Journal of British and Irish Innovative Poetry, we introduce the issue's seven articles, and share some speculations about the nature of the secret in its relation to poetry.